2011
DOI: 10.1007/s00199-011-0609-7
|View full text |Cite
|
Sign up to set email alerts
|

Herding with collective preferences

Abstract: This paper studies a simple model of observational learning where agents care not only about the information of others but also about their actions. We show that despite complex strategic considerations that arise from forward-looking incentives, herd behavior can arise in equilibrium. The model encompasses applications such as sequential elections, public good contributions, and leadership charitable giving.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 19 publications
(15 reference statements)
1
48
1
Order By: Relevance
“…It also includes models where agents communicate signals or beliefs, such as Eyster and Rabin (2011), Acemoglu et al (2014), andFan et al (2012), as well as models in which agents have collective preferences, such as Ali and Kartik (2012). Jackson (2007) and provide excellent surveys of the field.…”
Section: Related Literaturementioning
confidence: 99%
“…It also includes models where agents communicate signals or beliefs, such as Eyster and Rabin (2011), Acemoglu et al (2014), andFan et al (2012), as well as models in which agents have collective preferences, such as Ali and Kartik (2012). Jackson (2007) and provide excellent surveys of the field.…”
Section: Related Literaturementioning
confidence: 99%
“…In the original rational herding literature (e.g., Banerjee, 1992;Bikhchandani, Hirshleifer, and Welch, 1992) each player's payoff is assumed to be determined only by his decision but not by others. Dekel and Piccione (2000) and Ali and Kartik (2012) are among the papers that theoretically study sequential voting in collective decision making where payoffs are intrinsically interdependent. Unlike the expert signal in our setup, which is exogenously given to all voters, public information in their models is generated endogenously by the observed choices of earlier voters.…”
Section: Introductionmentioning
confidence: 99%
“…Dekel and Piccione (2000) show that the multiple equilibria include an equilibrium where all voters vote sincerely, which is informationally efficient. Ali and Kartik (2012) identify equilibria that exhibit herding whereby after observing some votes, the rest vote according to what the earlier votes indicate, regardless of their private information. Hung and Plott (2001) conducted a laboratory experiment on sequential voting with majority rule, and found that herding occurred, resulting in inefficiency with respect to sincere voting, while herding behaviour was not as pronounced as in the case where, like the standard herding literature, each subject's decision affected their individual payoff only.…”
Section: Introductionmentioning
confidence: 99%
“…2 However, even this does not help much in narrowing the scope of this survey. According to one of the Cambridge University Press webpages, 3 "Positive Political Economy investigates how observed differences in institutions a¤ect political and economic outcomes in various social, economic, and political systems." If one opens up the book, it turns out to be a collection of essays on various topics in macroeconomics and econometrics.…”
Section: Introduction and Overviewmentioning
confidence: 99%
“…It is also the title of a monograph series published by Routledge. 3 http://www.cambridge.org/us/catalogue/print.asp?isbn=9780521572156&print=y or the previous edition of the volume that covers political science experiments. Yet, some of the chapters, most notably the chapter on public goods (Ledyard 1996), cover material that could easily be categorized as political science; some of the seminal contributions in these areas were made by political scientists, explicitly with application to political science in mind.…”
Section: Introduction and Overviewmentioning
confidence: 99%